Efektivitas Model Pembelajaran Problem Based Learning Berbantuan Canva Terhadap Pemahaman Konsep Sistem Koloid Siswa Kelas XI SMAN 1 Girsang Sipanganbolon - Sihombing, Imanuel Gideon; Pane, Eva Pratiwi; Manurung, Hisar Marulitua (UNIB Press, 2025)
The purpose of this study was to determine the effectiveness of the Problem-Based Learning model assisted by Canva on the understanding of colloid system concepts among 11th grade students at SMAN 1 Girsang Sipanganbolon using an experimental research method with a quasi-experimental design. Data collection techniques used a multiple-choice test validated by expert validators, with instruments consisting of problem-solving ability test questions. The research subjects were 60 students from Grade XI Science Class 2 and Grade XI Science Class 4. Data analysis techniques included normality tests, homogeneity tests, and hypothesis testing using the paired sample t-test.The results obtained in this study indicate an improvement in the learning outcomes of grade XI students at SMAN 1 Girsang Sipanganbolon, particularly in the subject matter of colloid systems. This improvement in learning outcomes can be seen from the average pretest score of 49.67 and the average posttest score of 84.67 in the experimental class. These scores indicate a significant improvement in student learning outcomes. The homogeneity test was conducted, and the significance value obtained was greater than 0.05 (> 0.05), thus meeting the criterion where the sample is homogeneous. In the paired sample t-test, the t-value obtained was 18.542, which is greater than the t-table value of 1.699, and the sig (two-tailed) was 0.000, which is smaller than the α value (0.05), thus concluding that the problem-based learning model assisted by Canva is effective in improving students' understanding of colloid systems in grade XI at SMAN 1 Girsang Sipanganbolon.